Balancing Family and Career on the Academic Tightrope - Penney, Sharon Charlotte (Canadian Journal of Higher Education, 2015)
This qualitative research project explored the experiences of women who juggle the demands of family or parenthood while engaging in academic careers at a faculty of education. The researcher-participants consisted of 11 women; 9 women provided a written narrative, and all women participated in the data analysis. The data consisted of the personal, reflective narratives of 9 women who participated in a faculty writing group. Analysis of narratives uncovered 5 themes common to the researchers and participants in this study: genderspecific experiences surrounding parenting, second-career academics, pressure surrounding academic work, human costs, and commitment to work and family. Implications of the findings are discussed with particular emphasis on how a faculty writing group framed by a relational model of interaction can be used to support untenured faculty who experience difficulty balancing the demands of family and academia.